The representation of knowledge in contemporary times (Advances in Knowledge Representation, 2022)
From a postmodern perspective, the traditional view of the process of knowledge construction based on rationality is put in check. From the same perspective, the parameters of a modern science, based on a belief of a simplification of reality and in the search for formal causalities, are questioned. Thinking about knowledge representation in contemporaneity must, therefore, consider that knowledge and its construction involve plural processes that are anchored in sociocultural contexts. Reflecting on knowledge representation in the context of Library and Information Science (LIS), consequently, presupposes understanding how knowledge is constructed from its records, also called documents. Moreover, it presupposes reflecting on how such construction and the process of its representation are profoundly dependent on pragmatic and sociocultural contexts. Taking as a premise this relationship between knowledge, its representation and the influences of the contexts where they are generated and/or interpreted, our objective is to reflect on the foundations of the field of Knowledge Organization (KO) and, more specifically, Documentary Analysis (DA). Here we understand DA both as a methodological discipline that guides knowledge representation itself within the broader field of KO, and as a specific activity through which knowledge records – documents – are analyzed, synthetized and represented. From a methodological point of view, we will list the main differences between the modern and postmodern views on the process of knowledge construction, we will discuss the consequences for its representation in the scope of KO, and we will reflect on the pragmatic parameters involved in the operations performed upon knowledge in contemporaneity.